A Rare Case of Mucoepidermoid Carcinoma of the Nasal ala - Akbaridilmaghani, Nader; Iranpoor, Fatemeh; Etebari, Atefe (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Mucoepidermoid carcinoma is a malignant disease of salivary glands that originates from epithelial cells. These tumors are aggressive and have a poor prognosis. Aim: This study aims to investigate a rare case of nasal mucoepidermoid carcinoma of the nasal ala, and cover the general aspects of the pathogenesis and diagnosis. Case presentation: We reported a case of nasal ala mucoepidermoid carcinoma of unknown origin in a 73-year-old male patient without any symptoms or signs. Conclusion: Mucoepidermoid carcinoma usually involves the ethmoid area and its occurrence in the nose is very rare. Therefore, its formation in this area can be challenging and may not be correctly diagnosed. Therefore, in these cases, accurate and timely diagnosis can be vital for the patient and it is necessary to consider the possibility of mucoepidermoid cancer in the differential diagnosis when faced with a tumor in the nasal area.